2005
DOI: 10.1017/s0031182005008516
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a putative protein disulfide isomerase from Babesia caballi

Abstract: We produced a mAb against the Babesia caballi extracellular merozoite termed mAb 2H2 and used it to screen a cDNA expression library prepared from B. caballi merozoite mRNA for highly expressed proteins. The complete nucleotide sequence of the cloned gene had 1547 nucleotides and contained a 36-nucleotide intron. The 1398 nucleotide open reading frame predicts a 51 kDa protein showing similarity to protein disulfide isomerase (PDI) from other species. The PDI gene had a predicted N-terminal signal sequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, it was with the appearance of Gated Graph Neural Networks [23] and especially Graph Convolutional Networks (GCNs, [19]) that GNNs gained traction. A review and a unified notation for GNNs can be found in [2]. Fig.…”
Section: Graph Neural Network Basicsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it was with the appearance of Gated Graph Neural Networks [23] and especially Graph Convolutional Networks (GCNs, [19]) that GNNs gained traction. A review and a unified notation for GNNs can be found in [2]. Fig.…”
Section: Graph Neural Network Basicsmentioning
confidence: 99%
“…Because of its simplicity, we build on the GCN block to provide the reader with an intuition of how GNNs work. Following the notation proposed in [2], GCN blocks operate over a graph G = (V , E), where V = {v i } i=1:N v is a set of nodes, being v i the feature vector of node i and N v the number of vertices in the graph. E = {(s k , r k )} k=1:N e is a set of edges where s k and r k are the source and destination indices of edge k and N e is the number of edges in the graph.…”
Section: Graph Neural Network Basicsmentioning
confidence: 99%
See 2 more Smart Citations
“…GABA A R-induced fast-hyperpolarizing inhibition relies upon the low intracellular concentration of chloride. The potassium chloride cotransporter 2 (KCC2) is the neuron-specific member of the SLC12A family of cation-chloride cotransporters, which mainly extrudes neuronal chloride in adult central nervous system [69, 70]. Previous investigations elucidated that KCC2 was in charge of an inwardly directed electrochemical gradient of chloride and subsequently generated GABA A receptor-induced hyperpolarizing inhibitory responses in adult brain [71, 72].…”
Section: The Long-range Mode In Tae: Loss Of Gabaergic Interneurons Amentioning
confidence: 99%